2018
DOI: 10.1186/s13717-018-0114-z
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and habitat-suitability relationship deteriorate in fragmented forest landscapes: a case of Adinandra griffithii Dyer, a threatened endemic tree from Meghalaya in northeast India

Abstract: Introduction: A strong positive 'abundance and habitat-suitability' relationship is crucial for conservation of species. Nevertheless, anthropogenic alteration of natural landscapes leading to land use and land cover change, habitat loss, and species extinctions (may) have putatively disturbed this relationship. Hence, it is important to study the nature of the relationship in such human influenced landscapes. Methods: In this study, we endeavored to understand the consistency of the relationship in the fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
(38 reference statements)
0
4
1
Order By: Relevance
“…As previously suggested (Muñoz et al, 2015;Jiménez-Valverde et al, 2021), our results indicate that linear regressions tend to mask more complex relationships between abundance and HSI. Studies investigating the linear relationship between local abundance and HSI have reported a generally positive relationship (Tellería et al, 2012;Weber et al, 2017;Lunghi et al, 2018) but not consistently associated with a strong correlation (Bean et al, 2014;Adhikari et al, 2018). In our study, the residuals of the linear models between mean and maximum local abundances with HSI exhibit non-constant variances along the range of predicted values (Appendix S5), thus violating one of the assumptions of linear regressions.…”
Section: Discussioncontrasting
confidence: 52%
“…As previously suggested (Muñoz et al, 2015;Jiménez-Valverde et al, 2021), our results indicate that linear regressions tend to mask more complex relationships between abundance and HSI. Studies investigating the linear relationship between local abundance and HSI have reported a generally positive relationship (Tellería et al, 2012;Weber et al, 2017;Lunghi et al, 2018) but not consistently associated with a strong correlation (Bean et al, 2014;Adhikari et al, 2018). In our study, the residuals of the linear models between mean and maximum local abundances with HSI exhibit non-constant variances along the range of predicted values (Appendix S5), thus violating one of the assumptions of linear regressions.…”
Section: Discussioncontrasting
confidence: 52%
“…Medium resolution RS‐only SDMs are also very useful for predicting rare plant occurrences. Suitable habitats for the endemic tree Adinandra griffithii Dyer were accurately predicted (AUC = 0.99) by using EVI time series (Adhikari et al., 2018). Similarly, robust predictions were achieved for the narrow‐range endemic species Antirrhinum lopesianum Rothm.…”
Section: Remote Sensing Indirect Approach—prediction Of Rare Plant Distributionsmentioning
confidence: 99%
“…& Kurita, because of its sprouting period (early spring) and rapid growth, could directly contribute to the spectral information captured in early May, which was one of the most important predictors for both species. Likewise, the flowering phenological stage of the endemic tree A. griffithii played an important role in predicting its distribution, since the EVI for the periods of June and July were the most influential predictors (Adhikari et al., 2018).…”
Section: Remote Sensing Based On the Characteristics Of Rare Plantsmentioning
confidence: 99%
“…Moreover, the highly specific ecological niches of these species may also hinder their dispersal and range expansion as has been observed in some other threatened species including Adinandra griffithii ( Adhikari et al 2018 ) and Magnolia rabaniana ( Mir et al 2017 ). Since these species are confined to alpine and sub-alpine habitats which experience severe climates like high humidity, subzero temperatures and acidic soils which prevents them to acclimatize outside their natural setting ( Qu et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%